THE EFFECT OF THE HUMANISTIC SCIENCE LEARNING APPROACH ON THE SCIENTIFIC LITERACY ABILITY OF GRADE VIII STUDENTS AT SMP IT YAA BUNAYYA MAKASSAR - Wirawan, Zose; Tahir, Nur Ismi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to determine the effect of the humanistic science learning approach on the scientific literacy skills of eighth-grade students at SMP IT Yaa Bunayya Makassar. The humanistic science approach is a learning strategy that emphasizes a balance between mastery of scientific concepts and the development of human, moral, and social values. This study employs a quantitative method with a quasi-experimental design in the form of a pretest-posttest control group design. The research subjects consisted of two classes, namely the experimental class taught using a humanistic science approach and the control class which received conventional learning, each totaling 28 students. Data were collected through scientific literacy tests, observations, and documentation, then analyzed using an independent t-test and the N-Gain Score. The results showed that there was a significant difference between the posttest scores of the experimental and control groups with a calculated t-value = 4.82 > t-table = 2.004 (p = 0.000 < 0.05). The average N- Gain value of the experimental group was 0.60 (medium-high category), while the control group was 0.30 (medium-low category). The highest increase was in the socio-scientific context dimension with an N-Gain of 0.62, indicating that students were better able to relate scientific concepts to social reality. Thus, the humanistic science learning approach has a significant effect on improving students' scientific literacy skills, especially in developing conceptual understanding, scientific thinking skills, and social awareness. This approach has also been shown to foster scientific attitudes such as responsibility, empathy, and curiosity. The results of this study confirm that science learning that integrates human values can be an effective strategy in realizing meaningful and character-based science education.